Enhancement of YTHDF2 plays a protective role in acute IRI models through downregulation of TUG1 expression - Hong-Fei He; Shuang Hou; Xiao-Ya Ma; Song-song Huang; Bo Yang; Jun-Kang Wang; Yuan Xu; Lei Tan; Hai-Yang Li (PLoS ONE, 2025)
As one of the major causes of acute kidney injury, renal ischemia-reperfusion is a common health problem in a series of clinical situations, including renal transplantation. Although the mechanisms of renal IRI have been widely investigated, effective strategies are still in lacking for its prevention and treatment. In previous study, we found that the down-regulation of taurine upregulated gene 1, a long non-coding RNA (lncRNA TUG1), markedly alleviated renal IRI through mitigating the cell inflammation and apoptosis. At meanwhile, YTHDF2, an RNA methylation reading protein, was identified as a vital player in IRI of distinct organs, however, not reported in kidney. We then conducted the current study on the function of YTHDF2 in renal IRI and its regulatory role to TUG1. Based on renal IRI models in vitro and in vivo, dramatical down-regulation of YTHDF2 was presented. Subsequently, exogenous perturbation of YTHDF2 was conducted and its protective effects on cell apoptosis were demonstrated in acute IRI exogenous. Furthermore, with the same model, it was indicated that YTHDF2 protein negative regulated TUG1 RNA via direction interaction. Since then, YTHDF2 was proved as a potential protector of renal IRI through restraining of TUG1. In further speculation, induction of YTHDF2 in IRI will possibly become a possible strategy to combat the pathological process post renal transplantation or other clinical conditions.